The Influence Of Sedimentation On The Use Of The Pacal Reservoir In Bojonegoro District, East Java, Indonesia - Mushthofa; Indriani, Yulia; Nisa, Khoiru; Roesdina, Tira; Qomaruddin, Mochammad; Faqih, Nasyiin (Pt. Anagata Sembagi Education, 2024)
Pacal Reservoir is located in Kedungsource Village, Temayang District, Bojonegoro Regency, which functions to dam water from the Kedung River, which is a tributary of the Bengawan Solo River. Sedimentation is one of the main problems that occur in reservoirs, which causes a decrease in the operational life of the reservoir. Changes in land use can affect the sedimentation of the Pacal reservoir. This is caused by factors such as erosion, transportation and sedimentation that occur on the land. Changes in land use can increase land erosion, which can then increase sedimentation in reservoirs. This research aims to determine the level of sedimentation and its effect on the useful life of the Pacal Reservoir. From the research results, several conclusions were drawn relating to the sedimentation rate value in Pacal Reservoir in the 2013-2022 period as follows: The volume of suspended load was 24217.74 tons/year; Bed load volume is 45205.50 m³/yr; then the total value of sediment inflow is 92025.99 tons/year; The total sediment spread is 0.98 mm/yr. From the results of sedimentation calculations, the estimated remaining useful life of Pacal Reservoir is 30 years.